Strategi Pembinaan Tahsin Al-Qur’an dalam Kegiatan Tadarus Harian di SMP Babussalam Pekanbaru - Sundayu, Citra; Khoeriyah, Haniatul; Ach Flirdaus, Fiernando; Nuraini, Fitria; Safrizal, Safrizal (UIR Press, 2025)
The varying levels of Quranic reading ability among students at Babussalam Junior High School in Pekanbaru require Islamic Education teachers to implement effective tahsin strategies so that daily Quran recitation sessions can truly improve students’ Quranic reading skills. The purpose of this study is to analyze and understand the Quranic tahsin coaching strategies implemented by Islamic Education teachers during daily Quran recitation sessions at Babussalam Junior High School in Pekanbaru. This study uses a descriptive qualitative approach to understand the Quranic recitation improvement strategies of Islamic Education teachers at Babussalam Junior High School in Pekanbaru through daily recitation sessions. Data were collected through observation, interviews, and documentation, then analyzed to identify patterns and the impact of these strategies on students’ Quranic reading ability, fluency, tajwid, motivation, and religious culture. The results of the study indicate that the Quran reading abilities of students at Babussalam Junior High School in Pekanbaru vary widely, ranging from those who are proficient to those who are just learning the Arabic alphabet. A systematic and continuous tahsin coaching strategy by the Islamic Education teacher—including initial ability assessment, the talaqqi and simak methods, daily recitation, a focus on the articulation points of letters and tajwid, as well as individual guidance and peer tutoring—has proven effective in improving students’ fluency, accuracy of recitation, understanding of tajwid, motivation, and self-confidence. Efforts to enhance effectiveness—such as flexible learning groups, structured modules, collaboration with parents, teacher competency development, the use of audio-visual media, and a tiered appreciation culture—strengthen the quality of learning and foster students’ love for the Qur’an.